Crowdsourcing avant la lettre: Henri Cordier and French Sinology, ca. 1875-1925 - Chang, Ting (Johns Hopkins University Press, 2016)
This article argues that the French sinologist Henri Cordier (1849-1926) used his private correspondence with a vast international network of diplomats, administrators, missionaries, writers and scholars of every field of Asian studies between the 1870s until his death in 1926 to produce knowledge about China. Indeed, his unpublished correspondence, housed in the Bibliothèque de l’Institut de France in Paris, demonstrates a collaborative knowledge production on a global scale long before the digital revolution. Moreover, Cordier’s letters further show his correspondents giving him guidance or professional mentoring at a crucial moment in the development and professionalization of European sinology.